Visions of Law Enforcement Technology in the Period 2024-2034 Report of the Law Enforcement Futuring Workshop - Silberglitt, Richard (RAND Corporation, 2015)
This report presents the result of the July 2014 Law Enforcement Futuring Workshop, in which a diverse group of law enforcement practitioners explored future visions of law enforcement and identified and prioritized needs in technology, policy, and practice based on those visions.